Facing covid-19 in Ecuador: a blueprint for monetary policy and food sovereignty - Katiuska King; Pablo Samaniego; César Carranza (Revue de la Régulation)
In Ecuador, in a context of social and political conflict, the pandemic has revealed structural problems that are becoming increasingly acute for a country with a dollarized economy. The situation has its roots in inequality resulting from a number of sources and which has become more evident during the pandemic. A compounding factor is the dislocation of a population obliged to turn to informal work or self-employment due to the application of structural adjustment policies and deregulation of markets. The government boosts large-scale mining. Within this framework, the article proposes measures that could help to mitigate some of the problems faced by a country that does not have its own currency. A major component is a what we call conditional integral regulation, together with lines of liquidity which would promote the repatriation of capital. In terms of food sovereignty, while food is available, distribution problems in an agricultural sector based on the campesino and family economy are exacerbating a situation of chronic malnutrition in children.